2015
DOI: 10.1590/0034-737x201562050010
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of common bean in straw mulch systems and topdressing nitrogen rates in no-tillage

Abstract: In no-tillage systems, straw coverage on soil surface is the key to success, and the choice of crops for rotation is crucial to achieve the sustainability and quality that conservation agriculture requires. The objective of this study was to evaluate the agronomic performance of the common bean cultivar IAC Formoso sown in succession to three straw mulch systems (corn alone, corn/Urochloa ruziziensisintercrop and U. ruziziensisalone) and topdress nitrogen rates (0; 40; 80; 120 and 160 kg ha-1N), at the four-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In this crop system, the amount of straw on the soil surface increased significantly (totaling 8.6 ton ha -1 ), favoring the soil cover (100%) for subsequent crop sowing. Similar results were verified by Cunha et al (2015), in addition the authors emphasized that the corn and Congo grass modality is an excellent option for increase the deposition and straw persistence in the soil, even in Cerrado region, where the predominant environmental conditions favor the decomposition rate of organic residues. According to Correia et al (2013), for the prevailing weather conditions in the north of São Paulo State, it is recommended that the sowing of at least 200 points of cultural value of Urochloa seeds in row is sufficient to maintain adequate amount of straw on the soil for the viability and success of the no-tillage system.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In this crop system, the amount of straw on the soil surface increased significantly (totaling 8.6 ton ha -1 ), favoring the soil cover (100%) for subsequent crop sowing. Similar results were verified by Cunha et al (2015), in addition the authors emphasized that the corn and Congo grass modality is an excellent option for increase the deposition and straw persistence in the soil, even in Cerrado region, where the predominant environmental conditions favor the decomposition rate of organic residues. According to Correia et al (2013), for the prevailing weather conditions in the north of São Paulo State, it is recommended that the sowing of at least 200 points of cultural value of Urochloa seeds in row is sufficient to maintain adequate amount of straw on the soil for the viability and success of the no-tillage system.…”
Section: Resultssupporting
confidence: 76%
“…Among the main aspects related with viability and expansion of the crop in the offseason is the evolution of conservationist production systems, such as no-tillage and cultivation strategies with perennial forages, especially Urochloa species (Pariz et al, 2009;Chioderoli et al, 2012). Among the forages intercropped with corn, Congo grass (Urochloa ruziziensis) distinguish due to rapid establishment and excellent formation of straw, considering that the forage produces large amount of dry matter until sowing of the next crop, giving full protection to the soil surface (Souza et al, 2011;Freitas et al, 2013;Cunha et al, 2015). Furthermore, Urochloa species are considered great restorer of soil organic matter, in addition to promoting higher nutrient cycling in agricultural production systems (Batista et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the common bean grown after U. ruziziensis and corn in sole crops, the maximum N rate applied (160 kg ha -1 ) did not allow a maximum yield, with an increasing linear behavior in both situations, but with superiority after U. ruziziensis in sole crop (Figure 2A). When evaluating the agronomic performance of the IAC Formoso cultivar in three straw systems (sole corn, corn intercropped with U. ruziziensis and sole U. ruziziensis), and as a function of topdressing N fertilization (0 kg ha -1 , 40 kg ha -1 , 80 kg ha -1 , 120 kg ha -1 and 160 kg ha -1 ), Cunha et al (2015) observed higher yields in succession to U. ruziziensis in sole crop and intercropped with corn, with the benefits of (1) Means followed by equal letters do not differ by the Tukey test (p < 0.05). ** p < 0.01, * p < 0.05 and ns not significant, by the F test.…”
Section: Resultsmentioning
confidence: 99%
“…In the grain-filling stage, these reserves are broken, translocated and stored in these organs in the form of proteins and amino acids. In addition, N fertilization, besides promoting increases in yield (Cunha et al 2015, Soratto et al 2017, also stands out in the increase of grain protein content (Silva et al 2006, Farinelli & Lemos 2010, Amaral et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Seed yields in these fields are low, averaging just 0.9 Mg ha -1 (CONAB, 2017), due to a wide range of biotic and abiotic factors including drought, nutritional deficiency, weeds, and pests (Broughton et al, 2003). The use of cover crop mixtures may increase seed yield of common bean by improving chemical, physical, and biological soil properties: some studies have reported a higher number of pods per plant (Mingotte et al, 2014), increased average seed weight (Mingotte et al, 2014;Cunha et al, 2015), and overall greater yield of common bean when used in a cover crop rotation (Sabundjian et al, 2013;Mingotte et al, 2014;Amaral et al, 2016). Nitrogen is the most limiting nutrient for common bean production (Fageria and Baligar, 2005), and it is an essential element of amino acids, proteins, nucleic acids, and chlorophyll (Frink et al, 1999).…”
Section: Introductionmentioning
confidence: 99%